2018
DOI: 10.4236/ijmpcero.2018.72017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Distinct Radiotherapy Techniques to Induce Second Cancer Risks in Left Breast Cancer

Abstract: Influence of distinct radiotherapy techniques to induce second cancer risks in left breast cancer. Material and methods: Ten female patients with intact left breast cancer. Two treatment plans for each patient: 1) two tangential beams 3D-Conformal radiotherapy, 2) intensity-modulated radiotherapy (IMRT) plan. Estimation of second cancer risk from Organ equivalent dose models (OEDs) in three dose-response model for organs at risk in left breast cases. Results: The P-value for OED models in 3D-IMRT for left lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…It was observed that the risk using the ICRP model was significantly higher when comparing BEIR VII, and EPA models as shown the data in Figure 4 which show three models of ERR and EAR values This is consistent with the study by Amaoui et al [ 27 ] on the evaluation SCRs in breast cancer using the EAR and ERR from the ICRP models. They reported that the results are much higher (by around 19 times) than those calculated by Elgendy et al [ 28 ] on the estimation of SCRs in breast cancer. A limitation of the current study was that the results were based on 3D-CRT.…”
Section: Discussionmentioning
confidence: 68%
“…It was observed that the risk using the ICRP model was significantly higher when comparing BEIR VII, and EPA models as shown the data in Figure 4 which show three models of ERR and EAR values This is consistent with the study by Amaoui et al [ 27 ] on the evaluation SCRs in breast cancer using the EAR and ERR from the ICRP models. They reported that the results are much higher (by around 19 times) than those calculated by Elgendy et al [ 28 ] on the estimation of SCRs in breast cancer. A limitation of the current study was that the results were based on 3D-CRT.…”
Section: Discussionmentioning
confidence: 68%
“…Researches have demonstrated that using VW to treat breast cancer in comparison to intensity-modulated radiation therapy can reduce the risk of secondary cancer, OAR, and body radiation exposure. [ 12 13 ] Some studies have evaluated the dose calculation accuracy of various algorithms in the wedged field technique. Venselaar et al .…”
Section: Introductionmentioning
confidence: 99%